Biopolymer-based composites for tissue engineering applications: A basis for future opportunities. (1st June 2023) - Zarrintaj, Payam; Seidi, Farzad; Youssefi Azarfam, Mohamadreza; Khodadadi Yazdi, Mohsen; Erfani, Amir; Barani, Mahmood; Chauhan, Narendra Pal Singh; Rabiee, Navid; Kuang, Tairong; Kucinska-Lipka, Justyna; Saeb, Mohammad Reza; Mozafari, Masoud
Abstract: Biomimetic scaffolds supporting tissue regeneration are complex materials with multifunctional characteristics. The unique biocompatibility and biodegradability of biopolymers make them excellent candidates for tissue engineering and regenerative medicine. Biopolymers, which have a wide range of properties, can be obtained from different natural sources. Depending on the target tissue, biopolymers can be engineered to meet a series of specific functions. We review different types of biopolymers and their composites, besides their interactions with specific cells and tissues. Specific cellular mechanisms in tissue regeneration are also considered to elucidate the effects of biopolymers on controlling cellular mechanisms given their advantages and challenging aspects. Furthermore, the modifications required to mimic the properties of neural, cardiac, bone, and skin tissues are discussed. Utilization of biopolymer-based composites in tissue engineering requires additional improvements, where several challenges should be overcome. This work is mainly focused on biopolymers used in tissue engineering, providing support for engineering of future biocomposites for the same purpose. Some examples of biocomposites are also provided, a general guide for selection of biopolymers and the secondary component (biopolymers as complements, additives, or nano-scale biomaterials) to develop biocomposites.